Clinical profile of acute disseminated encephalomyelitis in children - Jayakrishnan, M.P. (Medknow Publications, 2010)
AIM: To study the clinical profile of acute disseminated encephalomyelitis (ADEM) in children. MATERIALS AND METHODS: All children admitted with ADEM during a period of one and a half years were included in the study. The diagnosis of ADEM was made based on the clinical presentation and suggestive MRI findings. All children were treated with intravenous methyl prednisolone, followed by oral prednisolone and followed up for varying periods up to three and a half years. RESULTS: The sample consisted of 14 children with 11(79%) girls and 3 (21%) boys. The oldest child was 12 years and the youngest was a six-month-old infant. Acute febrile illness preceded the onset of neurological symptoms in 64% of children. The interval between the preceding illness and symptoms of ADEM varied from 7 days to 28 days (mean 12 days). The common presenting symptoms were fever, vomiting, headache, gait disturbance and generalized seizures. Neurological manifestations included altered sensorium, multiple cranial nerve involvement, quadriplegia and paraplegia, dystonia and choreiform movements, nystagmus, bladder involvement (both incontinence and retention), speech defect and double vision. Facial nerve was the most common cranial nerve involved. Psychological manifestations included aggressive behavior, psychotic symptoms and mood changes. One child each had features of acute psychotic episode and depressive episode. All children recovered fully. One child had multiphasic disseminated encephalomyelitis (MDEM) on follow up. CONCLUSION: Despite the serious neuropsychiatric manifestations, ADEM in children generally has good immediate outcome. Children with ADEM need long-term follow up for cognitive impairments.